The THE EFFECT OF ZEOLITE DOSE ON THE CHARACTERISTICS OF SOIL AND RED CHILI YIELDS IN SUB-OPTIMAL LANDS OF COASTAL - Rajiman Rajiman; Ananti Yekti; Siwitri Munambar (Politeknik Negeri Lampung., 2021)
This study aims to determine the effect of zeolite dose on changes in some of the properties soil and red chilies yield. The research was conducted in the sandy land of the Bugel region, Kulon Progo Regency, from May to September 2020. The study used a randomized block design (RBD) with 5 replications. The study used a zeolite dose treatment consisting of Z0 = 0 kg/ha zeolite, Z1 = zeolite 200 kg/ha and Z2 = 400 kg/ha, Z3 = zeolite 600 kg/ha, Z4 = 800 kg/ha and Z5 = 1.000 kg/ha. The observation parameters consisted of texture, moisture levels of pF 4,2 and pF 2,54, moisture-holding capacity, volume weight, specific gravity, porosity, pH, C-organic, N-total, N-available, P-total, P-available, K total. , and K is available for coastal. The zeolite and manure were analyzed in the form of pH, C, N, P, K, and CEC. Plant parameters in the form of plant height, wet weight per plant, and weight of chilies per fruit. Soil observation data were analyzed descriptively. Analysis of plant data using Analysis of variance (ANOVA) and Duncan's Multiple Range Test (DMRT) 5%. The results showed that the increase in zeolite dose at coastal had increased clay content, moisture levels of pF 4,2 and pF 2,54, moisture-holding capacity, volume weight, density, soil pH, available N, available P, and K available, although they remained in the high category. The increase in zeolite dose at coastal did not significantly affect plant height 2-8 mst but did significantly affect the wet weight per plant and the weight of chilies per fruit.